Diagnosis of Aortic Graft Infection: A Case Definition by the Management of Aortic Graft Infection Collaboration (MAGIC). Issue 6 (December 2016) - Lyons, O.T.A.; Baguneid, M.; Barwick, T.D.; Bell, R.E.; Foster, N.; Homer-Vanniasinkam, S.; Hopkins, S.; Hussain, A.; Katsanos, K.; Modarai, B.; Sandoe, J.A.T.; Thomas, S.; et al.
Abstract : Objective/Background: The management of aortic graft infection (AGI) is highly complex and in the absence of a universally accepted case definition and evidence-based guidelines, clinical approaches and outcomes vary widely. The objective was to define precise criteria for diagnosing AGI. Methods: A process of expert review and consensus, involving formal collaboration between vascular surgeons, infection specialists, and radiologists from several English National Health Service hospital Trusts with large vascular services (Management of Aortic Graft Infection Collaboration [MAGIC]), produced the definition. Results: Diagnostic criteria from three categories were classified as major or minor . It is proposed that AGI should be suspected if a single major criterion or two or more minor criteria from different categories are present. AGI is diagnosed if there is one major plus any criterion ( major or minor ) from another category. (i) Clinical/surgical major criteria comprise intraoperative identification of pus around a graft and situations where direct communication between the prosthesis and a nonsterile site exists, including fistulae, exposed grafts in open wounds, and deployment of an endovascular stent-graft into an infected field (e.g., mycotic aneurysm); minor criteria are localized AGI features or fever ≥38°C, where AGI is the most likely cause. (ii) Radiological major criteria comprise increasing perigraft gas volume on serial computed tomography (CT) imaging or perigraft gas or fluid (≥7 weeks and ≥3 months, respectively) postimplantation; minor criteria include other CT features or evidence from alternative imaging techniques. (iii) Laboratory major criteria comprise isolation of microorganisms from percutaneous aspirates of perigraft fluid, explanted grafts, and other intraoperative specimens; minor criteria are positive blood cultures or elevated inflammatory indices with no alternative source. Conclusion: This AGI definition potentially offers a practical and consistent diagnostic standard, essential for comparing clinical management strategies, trial design, and developing evidence-based guidelines. It requires validation that is planned in a multicenter, clinical service database supported by the Vascular Society of Great Britain & Ireland.